Microstructural Characterization and Self‐Propagation Properties of Reactive Al/Ni Multilayers Deposited onto Wavelike Surface Morphologies: Influence on the Propagation Front Velocity. Issue 7 (1st March 2023) - Sauni Camposano, Yesenia H.; Bartsch, Heike; Matthes, Sebastian; Oliva-Ramirez, Manuel; Jaekel, Konrad; Schaaf, Peter
Abstract : Reactive multilayer systems are nanostructures of great interest for various technological applications because of their high energy release rate during the self‐propagating reaction of their components. Therefore, many efforts are aimed at controlling the propagation velocity of these reactions. Herein, reactive multilayer systems of Al/Ni in the shape of free‐standing foils with a wavelike surface morphology prepared by using sacrificial substrates with well‐aligned waves are presented and the propagation of the reaction along different directions of the reproduced waves is analyzed. During the ignition test, the propagation front is recorded with a high‐speed camera, and the maximum temperature is measured using a pyrometer. The propagation of the reaction is favored in the direction of the waves, which points out the influence of the anisotropy generated by this morphology and how it affects the propagation dynamics and the resulting microstructure. Furthermore, compared to their counterparts fabricated on flat substrates, these reactive multilayers with wavelike morphology exhibit a remarkable reduction in the propagation velocity of the reaction of about 50%, without significantly affecting the maximum temperature registered during the reaction. Abstract : Reactive multilayer systems are produced by using substrates with an anisotropic surface topography; as a result, the reactive system presents a wavy morphology that affects the dynamics of the self‐propagation process. The propagation of the flame will be favored in the direction of the waves, showing an atypical propagation front.